Comparative analyses and investigations of chamfered and honed-edge tool geometries on tool wear, chip morphology, residual stresses and end-burr formation. (August 2022) - Asad, Muhammad; Ijaz, Hassan; Khan, Muhammad Azhar Ali; Khan, Mushtaq; Mabrouki, Tarek; Rashid, Muhammad Usman
Abstract: Cutting simulations for chamfered-edge and honed-edge tools for rough-to-semi finishing operations in machining an aerospace grade aluminum alloy AA2024 have been presented in this work. A finite element based approach has been developed to comprehend and investigate the relative effects of various cutting edge geometries on chip morphology, end-burr and residual stresses. Additionally, the role of chip-breaker geometry in segmentation and fragmentation has been thoroughly examined. Moreover, to estimate the expected wear in different sections of the tool, stress fields have been plotted. Furthermore, effects of chamfered-tool' macroscopic parameters: chamfer-length and chamfer-angle on various aspects of cutting process have been discussed. Presented coupled temperature-displacement numerical model has been validated for various results concerning chip morphology, cutting forces and segmentation frequency with previously performed experimental work. Finally, recommendations are made for proper selection of tool-geometry for better tool life, surface integrity and lesser burr formation in machining AA2024. Highlights: For chamfered-edge tools, their equivalent honed edges are proposed. Honed tools cause lower residual stresses and uniform chips than chamfered tools. Chamfered-edge tools result in lesser burr lengths than honed tools. Fewer chances of edge failure for chamfered-edge tools in roughing operations. Chip-breaker geometry is vital in chip segmentation and fragmentation.